Pengaruh Kepercayaan, Keamanan dan Kualitas Pelayanan terhadap Keputusan Pembelian Barang secara Daring - Muhammad Tommy Arby Rumengan; Muhammad Tammy Ikbal Rumengan; Adnan Suhardis; Khairul Riza (Jurnal Bisnis dan Pemasaran Digital, 2022)
Purpose: The purpose of this study was to determine the effect of trust, security and service quality on online purchasing decisions on E-Commerce. Method: This type of research is quantitative research, namely research methods based on positivism philosophy, used to examine certain populations or samples. Result: The results of multiple regression analysis are Y = 9.064 + 0.588 + -0.011 + 0.318 + e which shows that trust, security and service quality have a positive and significant effect on purchasing decisions. While the results of the test (t) or partial test show that the price (0.000) is smaller than that of alpha 5% (0.05) or tcount = 3.961 > ttable 1.66792, it can be concluded that H1 is accepted which means there is an effect of X1 on Y The security variable (0.958) is greater than that of alpha 5% (0.05) or tcount = 0.053 < ttable 1.66792, it can be concluded that H2 is rejected which means there is no effect of X2 on Y. And the service quality variable (0.005) smaller than alpha 5% (0.05) or tcount = 2.870 > ttable 1.66792, it can be concluded that H3 is accepted, which means there is an effect of X3 price on Y. Conclusion: The results of the regression test in this study, the significance value is 0.000. Where it is required that the significance value of F is less than 5% (0.05) or the value of Fcount = 88.320 > Ftable 2.74, which means that there is an influence of the variables of trust, security and service quality (X1, X2, X3) simultaneously (together). ) on purchasing decisions on E-Commerce.